Selective Mapping of Brain COX-1 with [11C]PS13: Pharmacokinetic Evidence from human PET Imaging - Kiana Orangi; Kimiya Batebi; Farnoosh Vosough; Mahdiyeh Nozad Varjovi; Fatemeh Salehian; Sahar Mesbah; Mehrnaz Salahi; Sajjad Hajihosseini; Mohammad Yousef Fazel; Saman Zaman; Reza Hossein Zadeh; Alaleh Alizadeh; et al. (IBRO Neuroscience Reports)
Background and aim: Arachidonic acid is converted by cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) to prostaglandin H2, which has proinflammatory properties. The new PET radioligand [11 C]PS13 exhibits superior in vivo selectivity for COX-1 in nonhuman primates compared to COX-2. This study aimed to investigate [11 C]PS13 pharmacologically selectivity and substantial binding to COX-1 in the human brain. Material and methods: Eight healthy volunteers had baseline [11 C]PS13 brain PET scans, and then images were blocked with either aspirin, celecoxib, or ketoprofen. The participants underwent two 90-minute [11 C]PS13 PET scans with radio metabolite-corrected arterial input function at baseline and approximately two hours after they received 75 mg of ketoprofen orally Result: This study on [11 C]PS13 brain PET scans showed that ketoprofen and celecoxib selectively bind to COX-1 in the human brain. The occupancy plot showed a positive correlation with plasma ketoprofen concentration, with the highest binding potentials in the calcarine and lingual gyrus of the occipital region. The occupancy for COX-1 was about 49 % and 27 % for ketoprofen and celecoxib, respectively. Conclusion: Ketoprofen demonstrated the highest selectivity for COX-1, while celecoxib exhibited partial occupancy likely due to dose- or time-dependent COX-1 inhibition. Aspirin showed minimal effect. Given the small sample size (n = 8), further studies with larger cohorts are warranted to confirm these findings and assess pharmacokinetic influences more thoroughly.